Direct Current Electric Circuit-Visualization Skills Instrument Test (DCEC-ViSIT) to Measure High School Student’s Visualization Skills - Sundari, Resti; Suhandi, Andi; Samsudin, Achmad (FKIP Universitas Lampung, 2023)
This research aims to develop instrument test visualization skills on direct current electric circuits. The research method used is the development of a 4D model consisting of defining, designing, developing, and disseminating. The participants in this research consisted of 33 high school students in West Java who were randomly selected. The first analysis is an analysis of the results of expert validation using CVR, which is considered valid. The second analysis is the Rasch analysis, which obtained raw variance data with special interpretation and declared the questions valid. The third stage is the analysis of the parameters of the items included in the interpretation of